(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Globally, silver nanoparticles (SNP) were created using a biologically activated green synthesis process that has raised substantial awareness of medical science and illness therapy. A new method of synthesising SNPs based on a bottom-up, "green" approach is described here Guazuma ulmifolia Lam. leaf aqueous extract in addition to assess their antibacterial, anti-inflammatory also anticancer in vitro properties. By using well diffusion method, the antibacterial activity possessed by nanoparticles against Staphylococcus aureus, Staphylococcus gallinarium, Bacillus subtilis, Pseudomonas stuberia, in addition to Escherichia coli was examined. Subsequently, these GUSNPs (Guazuma ulmifolia Silver Nanoparticles) were investigated for anticancer activity assessed by MTT assay utilizing HepG2 carcinoma cell line, and anti-inflammatory activity assessed by HRBC stabilization assay protein denaturation assays. In dosage of 10 μg/ml, the GUSNPs had the maximum antibacterial activity against the following bacteria: Staphylococcus aureus (7.1 mm), Staphylococcus gallinarium (5.2 mm), Bacillus subtilis (6.7 mm), Pseudomonas stuberia (6.3 mm), and Escherichia coli (4.7 mm), respectively. Membrane stabilization of HRBCs had a substantial anti-inflammatory activity (73.27±0.89%), whereas the GUSNPs had the best protection of protein denaturation (79.35±0.42%) at 1000 μg/ml. The best cytotoxicity activity of GUSNPs against HepG2 cell line was found in 500 μg/ml concentration with 24.32 percent of cell viability. The current study of GUSNPs has good antibacterial, anti-inflammatory, and anticancer activities.